Wired/Wireless Internet Communication 11th International Conference, WWIC 2013, St. Petersburg, Russia, June 5-7, 2013. Proceedings - Tsaoussidis, Vassilis; Kassler, Andreas J.; Koucheryavy, Yevgeni; Mellouk, Abdelhamid; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the refereed proceedings of the 11th International Conference on Wired/Wireless Internet Communications, WWIC 2013, held in St. Petersburg, Russia, during June 5-7, 2013. The 21 revised full papers presented were carefully reviewed and selected from numerous submissions. The papers are organized in topical sections on: MAC and scheduling; mobility; fixed networks; services and security; sensor networks; services; and wireless.
MAC and scheduling -- Mobility -- Fixed networks -- Services and security -- Sensor networks -- Services -- Wireless.
Keywords: Computer science; Computer Communication Networks; Operating systems (Computers).; Data protection; Computer Science; Computer Communication Networks; Systems and Data Security; Information Systems Applications (incl. Internet).; Operating Systems